A Parametric Study on Friction Instabilities in Mechanical Face Seals. Issue 5 (2nd September 2016) - Valigi, Maria Cristina; Braccesi, Claudio; Logozzo, Silvia
ABSTRACT: The present article aims to analyze and evaluate how dynamic parameter design influences the behavior of mechanical face seals and improves their performance by detecting undesirable phenomena like stick–slip and ringing. Those phenomena occur in situations of boundary lubrication. A new lumped parameter model is proposed to study mechanical face seals used in automotive cooling water pumps in order to examine how dynamic parameters such as mass, moment of inertia, and stiffness are involved in stick–slip phenomena. The aim of this work is to provide a practical design tool to predict stick–slip conditions and to choose the optimal mechanical specifications. Numerical simulations demonstrate how the critical service conditions vary with design parameters and permit tabulation of the results.